Interim Report Task 2B - Community Consultation on Wall Construction Methods - Cornick, S. M.; Rousseau, M. Z. (National Research Council of Canada, 2007)
This document is the collection of community consultation notes summarizing input received during 3 consultation sessions which NRC-IRC researchers conducted in Whitehorse YT, Yellowknife NT and Arviat NU in February 2007.The objective of these consultations was to establish a dialogue with northern communities on their needs and constraints related to housing projects, as well as their experience with the applicability and performance of different construction methods for exterior walls in an arctic context. : Ce document regroupe les notes résumant l'information obtenue lors de 3 séances de consultation communautaire que des chercheurs de l'IRC-CNRC ont tenu à Whitehorse YT, Yellowknife TNO and Arviat NU en février 2007. Ces consultations avaient pour but d'établir un dialogue avec les communautés du Nord concernant les besoins et les contraintes associés aux projets d'habitations ainsi que leur expérience au sujet de l'applicabilité et la performance des diverses méthodes de construction des murs extérieurs dans l'Arctique. : Aussi disponible en français: Rapport provisoire, TÂCHE 2B - Consultation des collectivités locales sur les méthodes de construction des murs